Abdul Rashid Moten, Revolution to revolution: Jama'at-e-Islami in the politics of Pakistan (Kuala Lumpur: Islamic Book Trust in association with International Islamic University Malaysia, 2002) 201 pages. - Hossain, Ishtiaq (Taylor & Francis, 2003)
The study of social movements has mushroomed from a marginalised field of study in social psychology in the 1960s to a large speciality area of sociology in its own right with significant ties to political, organisational, and cultural sociology. Jama'at-e-Islami, which first began its journey as an Islamic social movement is the object of research by Abdul Rashid Moten. Employing, a political-sociological method — the elite theory — in Revolution to Revolution: Jama'at-e-Islami in the Politics of Pakistan, Abdul Rashid Moten provides a fascinating and perceptive analysis of the transformation of the Jama'at from an Islamic social revivalist movement to a full-fledged political party in Pakistan. The Jama'at-e-Islami was formed in 26 August 1941, with Sayyid Abul A'la Mawdudi being elected as its first amir. He resolutely believed in the unity of the Muslim Umma and considered nationalism as an alien concept to Islam. Therefore, he did not join the movement for the establishment of Pakistan. However, once this state came into being in 1947, Mawdudi moved to Pakistan and resumed the activities of the Jama'at.